STRATEGI SOSIAL MEDIA DANA.ID DALAM MENINGKATKAN BRAND IMAGE (Studi Kasus Content Creative 4.0 di Instagram) - Santoso, Ade Budi; Wijayanti, Isa; Romadon, Saiful (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Dana is an Indonesian digital wallet designed to make every non-cash and non-card transaction digitally, both online and offline, run quickly, practically and with guaranteed security. The purpose of this journal is to find out and examine how the Concept of Content Creative 4.0 PT. Espay Debit Indonesia in improving Brand Image and reviewing the Engagement Rate Content Creative 4.0 through Instagram @dana.id Media to increase Brand Image Users, Dana Followers. This research uses digital revolution theory, New Wave Marketing and Engagement Rate analysis. This research uses a qualitative approach with case study research methods and constructivist research paradigms. The results of this study are how Content Creative can improve Brand Image through Dana's Instagram social media, how through Content Dana tries to attract images with its consumers, this is in accordance with the concept of Content Marketing where the relationship between a Brand and its consumers is horizontal. In improving Brand Image through content on Instagram social media, Dana uses the elements contained in the New Content Marketing 7 (Seven) steps of Content Marketing, namely: setting goals, mapping targets, determining the major themes of the content presented, determining when and who makes Content, distributing Content, strengthening Content and evaluating. Brand Dana already has a strong character for online business activists because Brand Dana has 7 steps of Content Marketing.